Analisis Faktor yang Berhubungan dengan Nyeri Punggung Bawah pada Pekerja Industri Batu Bata di Desa Cipayung Kecamatan Cikarang Timur - Rini Puspita Dewi (Universitas Pahlawan Tuanku Tambusai, 2023)
Low back pain is pain that is felt in the lower back area, which is located between the corners of the lowest ribs and the sacrum. Organization (WHO) (2013) has identified that lower back pain is one of three health problems that should be a target for monitoring. Based on a preliminary survey conducted by researchers, it was found that several workers in informal industries complained of experiencing lower back pain when doing work or work. after doing the work. This research was conducted from February to April 2023. The sample in this research consisted of 38 workers in the brick industry spread across Cipayung Village. This research is a type of quantitative research with a cross sectional design. The statistical test used in this research is Chi-Square. The results of the bivariate test using Chi-Square showed that there were 2 variables related to Lower Back Pain, namely Sports Habits with a p-value of 0.028 (p<0.0) and Work Duration with a p-value of 0.006 (p<0, 0.0) 05), while the working period is not related to Low Back Pain with a p-value of 0.6 (p>0.05). Factors that are related to low back pain are duration of work and low back pain, while working time is not related to low back pain.